Coal bottom ash as an eco-friendly cement substitute in self-compacting concrete: Properties and potential - Al Biajawi, Mohammad I.; Rahimah, Embong (Semarak Ilmu Publishing, 2024)
In numerous nations, the utilization of coal as an energy source for thermal power plants and manufacturing operations has increased in recent decades, which has led to an increase in coal consumption. The growth of the world's population is reflected in the increasing use of cement in the construction industry and in the rising production of concrete worldwide. These two occurrences contribute significantly to the increase in carbon dioxide (CO2) emissions and coal ash discharges, both of which are harmful to the surroundings. Coal-fired power plants produce industrial byproducts such as coal-bottom ash (CBA) that could be incorporated into self-compacting concrete (SCC) to provide sustainable building materials and encourage the use of byproducts. Consequently, the objective of this experimental study is to investigate the effects of CBA as a cement substitute in SCC on the fresh and mechanical properties. Six various mixtures were prepared by replacing the cement used in the production with different amounts of CBA (0%, 10%, 20%, 30%, 40%, and 50%, respectively). The various properties of all mixtures, including fresh and mechanical properties of concrete, were analysed in accordance with EFNARC and ASTM standards. For the fresh concrete properties of the SCC, a slump flow test, an L-box test, and a V-funnel test were performed. For the mechanical properties, compressive strength, tensile strength, and water absorption tests were performed. The result showed that CBA can be use as cement replacement up to 20% exhibited to improve the strength of SCC Mixture.